Functional Performance of Chitosan/Carbopol 974P NF Matrices in Captopril Tablets. (25th October 2016) - Aguilar-López, Yuritze Alejandra; Villafuerte-Robles, Leopoldo
Abstract : Chitosan and Carbopol have been used to form a complex through an electrostatic interaction between the protonated amine (NH3 + ) group of chitosan and the carboxylate (COO − ) group of Carbopol. In situ polyelectrolyte complexes formations based on the physical mixture of chitosan and sodium alginate were found and could be used as an oral controlled release matrix. The aim of this work is the assessment of a possible interaction between the particles of chitosan and Carbopol 974P NF that could modify their technological performance in captopril tablets. The drug and excipients were evaluated as mixtures of powders and tablets. The mixtures with captopril contained Carbopol 974P NF, chitosan, or a 1 : 1 mixture thereof with polymer proportions of 10%, 20%, and 30%. The evaluated parameters were the powder flow rate, the powder compressibility index, and the compactibility and release behavior of the tablets. The observed technological behavior points out to a greater interaction between the particles of polymers with different charge than between particles of the individual polymers. This produces more coherent matrices restricting more efficiently the drug dissolution, more coherent tablets with higher compactibility, and less flowing powder mixtures. All this, however, requires additional investigation to confirm the current results.